The role of credible suppliers and perceived risk in motivating Malaysian Gen-Z to purchase blind boxes - Chua, Lian Qing; Ngoi, Jun He (2025)
The blind box market has gained significant popularity globally, particularly among younger consumers, by leveraging the elements of surprise and novelty. However, in Malaysia, this trend has not achieved the same level of engagement as in other regions. This study investigates the factors influencing Malaysian Gen-Z's intention to purchase blind boxes, focusing on supplier credibility (attractiveness, trustworthiness, and expertise) and perceived risk. Grounded in the Source Credibility Theory (SCT), the research integrates perceived risk as an additional variable to explore its impact on purchase intentions. A quantitative approach was employed, with data collected from 367 Malaysian GenZ respondents aged 12 to 25 through a cross-sectional survey. The findings reveal that perceived risk and supplier expertise significantly influence purchase intentions, while attractiveness and trustworthiness do not exhibit a statistically significant impact. Specifically, reducing perceived risk traits, such as financial concerns and quality uncertainty, enhances the likelihood of purchase. Additionally, suppliers' expertise in providing accurate information and proactive problem-solving positively affects consumer confidence. The study contributes to the literature by extending the SCT framework to the blind box context and highlighting the critical role of perceived risk in consumer decision-making. Practical implications suggest that marketers and policymakers should prioritize transparency, risk mitigation strategies, and supplier expertise to foster trust and encourage participation in the blind box market. Limitations include the cross-sectional design and gender imbalance in responses, which future research could address through longitudinal studies and broader demographic sampling.